Brother-making in late antiquity and Byzantium monks, laymen, and Christian ritual - Rapp, Claudia 1961- (Oxford University Press, 2016)
An exhaustive treatment of ritual brotherhood in Byzantium, this book challenges the 'Boswell Thesis' and argues that the ecclesiastical ritual to bless a relationship between two men bears no resemblance to marriage, but has its origins in early monasticism
Keywords: Christentum; Kirchengeschichte; Religion; Monastic and religious life / Byzantine Empire; Rites and ceremonies / Byzantine Empire; Homosexuality / Religious aspects / Christianity; Verbrüderung; Ritual; Byzantine Empire / Church history; Byzantinisches Reich